1992
DOI: 10.1113/jphysiol.1992.sp019240
|View full text |Cite
|
Sign up to set email alerts
|

Second‐messenger regulation of sodium transport in mammalian airway epithelia.

Abstract: SUMMARY1. Sodium absorption is the dominant ion transport process in conducting airways and is a major factor regulating the composition of airway surface liquid. However, little is known about the control of airway sodium transport by intracellular regulatory pathways.2. In sheep tracheae and human bronchi mounted in Ussing chambers under short circuit conditions, the sodium current can be isolated by pretreating tissues with acetazolamide (100 1uM) to inhibit bicarbonate secretion, bumetanide (100 /LM) to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…A variety of studies have been conducted in freshly isolated tissues, primary cultures, and cell lines from multiple species, but there is not a consensus as to the mechanism(s) responsible for inhibition of sodium transport. Most of the results support a role for calcium mobilization (13,21), but not PKC activation, despite evidence that direct activation of PKC with phorbol esters can lead to inhibition of amiloride-sensitive sodium absorption in airways (18,25). O'Grady and coworkers (30) recently reported that extracellular UTP elicited a transient stimulation of Cl secretion, followed by a sustained inhibition of amiloride-sensitive sodium absorption in cultured porcine endometrial epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A variety of studies have been conducted in freshly isolated tissues, primary cultures, and cell lines from multiple species, but there is not a consensus as to the mechanism(s) responsible for inhibition of sodium transport. Most of the results support a role for calcium mobilization (13,21), but not PKC activation, despite evidence that direct activation of PKC with phorbol esters can lead to inhibition of amiloride-sensitive sodium absorption in airways (18,25). O'Grady and coworkers (30) recently reported that extracellular UTP elicited a transient stimulation of Cl secretion, followed by a sustained inhibition of amiloride-sensitive sodium absorption in cultured porcine endometrial epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…Several receptor agonists cause acute and/or chronic downregulation of Na ϩ absorption, including epidermal growth factor (EGF) (10,32,43,46), acetylcholine and PGE 2 (6,15,17,46), and extracellular ATP (26). Several intracellular signaling pathways (i.e., PKC, calcium, Src kinase, ERK1/2) have been implicated (17,18,21,24,43,47); however, the precise molecular mechanisms responsible for inhibition of ENaC function have not been fully elucidated.ENaC belongs to the degenerin/ENaC gene superfamily, and functional channels are thought to be composed of some combination of three homologous subunits: ␣-, ␤-, and ␥-ENaC (7). Each subunit has the predicted membrane topology of two hydrophobic membrane-spanning regions, a highly conserved large extracellular cysteine-rich loop, and intracellular NH 2 and COOH termini.…”
mentioning
confidence: 99%
“…It might contribute to the increased Na ϩ absorption described in CF airway epithelia (45). Na ϩ absorption is reduced by stimuli causing cytosolic Ca 2ϩ increases (46,47). Therefore, a defective TRPV4 channel might result in a reduced mechanically induced Ca 2ϩ signal and increased amiloride-sensitive Na ϩ absorption.…”
Section: Discussionmentioning
confidence: 99%
“…An autocrine regulation of [Ca 2+ ] i by CFTR activation could stimulate Ca 2+ -activated Cl − current (Mason, Paradiso & Boucher, 1991;Urbach et al, 1994;Schwiebert et al, 1995). In addition, amiloridesensitive sodium absorption through epithelia has been shown to be indirectly inhibited by experimental manoeuvres designed to increase [Ca 2+ ] i (Graham et al, 1992;Ismailov, Berdiev & Benos, 1995;Harvey, 1995;Maguire et al, 1999). Therefore, the CFTR protein activation could control the balance between secretion and absorption by simultaneous stimulation of chloride secretion through other Cl − channels while downregulating sodium absorption in normal epithelia.…”
Section: Discussionmentioning
confidence: 97%